PHARMACEUTICAL RESEARCH IN ASIA: A BIBLIOMETRIC STUDY - Shilpa P. Shahare; Vaishali Khaparde; Deepa N. Gaikwad; Suraj M. Tayade; Jayshila K. Khandare; Rohini G. Landge; Amrapali K. Khandare (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The goal of the this study is to examine and evaluate research article of pharmaceutical research in Asia during the period 2018 to 2022 which is indexed in web of science. For that a total 486 research article was analyses using bibliometric approach through different parameters like type of document, authorship pattern, and year-wise distribution of articles, relative growth rate and doubling time growth rate, most productive country, author and affiliations. the study found that The highest number of contributions, 126 (25.93%), were published in 2021, during a five-year period, its relative growth rates and doubling time is increased, mean of relative growth is 0.37 and mean of doubling time is 0.42, most of the publication published as journal article with 370 (76.13%), The average number of authors per paper is 12.89, with a productivity of 0.078 per author, seven author collaboration contribute more 49 (10.08%), Kroon, E and Phanuphak, N shared first place with 14 (2.88%) articles each, University of London contributed the most articles, with 37 (7.61%), followed by Monash University in second place with 26 (5.35%), USA is the most productive country with 163 (33.54%) contribution , ‘COVID-19’ is highly used keyword, ‘Molecules’ is most productive Journal of articles.